Two Chloroplast Proteins Negatively Regulate Plant Drought Resistance Through Separate Pathways. Issue 2 (27th November 2019) - Hong, Yechun; Wang, Zhen; Liu, Xue; Yao, Juanjuan; Kong, Xiangfeng; Shi, Huazhong; Zhu, Jian-Kang
Abstract : The chloroplast proteins depress H2 O2 accumulation in guard cells and drought resistance through OST1-dependent and OST1-independent pathways. Abstract: Drought is one of the most deleterious environmental conditions affecting crop growth and productivity. Here we report the important roles of a nuclear-encoded chloroplast protein, PsbP Domain Protein 5 (PPD5), in drought resistance in Arabidopsis ( Arabidopsis thaliana ). From a forward genetic screen, a drought-resistant mutant named ppd5-2 was identified, which has a knockout mutation in PPD5 . The ppd5 mutants showed increased H2 O2 accumulation in guard cells and enhanced stomatal closure in response to drought stress. Further analysis revealed that the chloroplast-localized PPD5 protein interacts with and is phosphorylated by OST1, and phosphorylation of PPD5 increases its protein stability. Double mutant ppd5-2ost1-3 exhibited phenotypes resembling the ost1-3 single mutant with decreased stomatal closure, increased water loss, reduced H2 O2 accumulation in guard cells, and hypersensitivity to drought stress. These results indicate that the chloroplast protein PPD5 negatively regulates drought resistance by modulating guard cell H2 O2 accumulation via an OST1-dependent pathway. Interestingly, the thf1-1 mutant defective in the chloroplast protein THF1 displayed drought-resistance and H2 O2 accumulation similar to the ppd5 mutants, but the thf1-1ost1-3 double mutant resembled the phenotypes of the thf1-1 single mutant. These results indicate that both OST1-dependent and OST1-independent pathways exist in the regulation of H2 O2 production in chloroplasts of guard cells under drought stress conditions. Additionally, our findings suggest a strategy to improve plant drought resistance through manipulation of chloroplast proteins.